Sosialisasi Pendidikan Politik Pada Siswa Sebagai Sarana Menghadapi Pemilu Serentak Tahun 2024 - Rochim, Ahmad Abdul (STAI Publisistik Thawalib Jakarta, 2024)
This service activity aims to increase the understanding, participation and knowledge of the younger generation about politics in the era of general elections, especially students at the Bintang Sembilan Vocational School, Indramayu. This PKM activity carried out visits, Focus Group Discussions, and voting simulations by students. The equipment used is material books, office stationery, boxes and voting simulation paper. Based on the results of the implementation of this service activity, it can be explained that there has been an increase in students' political participation, knowledge, understanding and awareness and they have become more aware of the importance of political participation, both in the general election process and in overseeing regional development.